Factors Influencing Hematologists-Oncologists’ Prescription of Chemotherapy Drugs in Cancer Treatment in Iran: an Interview Questionnaire Study: Factors influencing hematologists-oncologists’ prescription of chemotherapy drugs - Seyed Abolfazl Abolfazli; Mehdi Mohammadzadeh; Farzad Peiravian; Seyed Hesam Sharifnia (Iranian Journal of Pharmaceutical Sciences, 2017)
Cancer can be treated by surgery, chemotherapy, radiation therapy, hormonal therapy, and targeted therapy. The choice of treatment depends on the type and stage of the cancer. Chemotherapy drugs play an important role in cancer treatment. The objective of this interview-questionnaire study is to explore what influences Iranian hematologists-oncologists’ prescription when prescribing chemotherapy drug. Data collection can be divided into two categories: the interview and the questionnaire. The qualitative part consists of depth interviews, utilizing closed- and open-ended questions, were conducted with oncologists, selected through theoretical sampling. The interview questions consisted of two parts, in the first part; open-ended questions were posed about factors influencing prescription. In the second part, the oncologists were asked to rate predefined factors that might influence their prescription decisions. The quantitative part of the study consists of questionnaire included two parts; the first part consisted of general questions including gender, age, membership in scientific committees and professional background. The second part consisted of 24 specialized questions that covered all the indexes of the effective factors on oncologists’ prescription decisions. Ten oncologists were interviewed. Factors affecting chemotherapy drug prescription were grouped into three categories based on qualitative studies carried out and is presented as they were mentioned and rated by the hematologists-oncologists: 1) Products properties, 2) Pharmaceutical marketing, 3) Scientific, experimental confirmation. The findings from the questionnaire suggest products properties particularly (clinical effectiveness) is the most important factor considered in drug prescription choice. Also, the socialized medicine sponsorship and clinical trial respectively are the most effective on increasing the frequency of prescribing. Whilst, prescribing by brand name or higher prices for a drug are not necessarily justified. The results of this study provide new insights to the nature prescribing behavior driven to develop measures which could be used to achieve greater clinical effectiveness and economic efficiency from drug prescribing.